Placental Mesenchymal Dysplasia, An Exceedingly Rare Entity and Challenging Diagnosis. (28th October 2021) - Hussain, F; Kumar, V; Prakash, V; Shenoy, V; Al Hmada, Y
Abstract: Introduction/Objective: Placental mesenchymal dysplasia (PMD) is an extremely rare entity with an incidence of only 0.02/1000 deliveries. Methods/Case Report: We present a case of a 26 year-old female Gravida 3, Para 1 with intrauterine pregnancy at 37 weeks of gestation. Fetal ultrasound showed mildly cystic upper portion of the placenta. The noninvasive prenatal testing was negative for triploidy. A viable healthy female infant was delivered with no maternal complications. On gross examination, placenta was heavy with approximately 25% incomplete cotyledons. Placental maternal surface showed, spongiform cut surfaces admixed with multiple cystic structures ranging in size from 0.5 to 1.5 cm and markedly dilated blood vessels. Histopathologic examination revealed markedly enlarged villi, mesenchymal hyperplasia, and hyper vascularity of small vessels. No trophoblast proliferation was identified. Subsequently, the diagnosis of PMD was made. Results (if a Case Study enter NA): NA Conclusion: PMD is a rare anomaly which is characterized by placentomegaly and grape like vesicles resembling molar pregnancy. Etiologies include imbalance of paternal and maternal alleles, androgenetic and bi-parental mosaicism, and Beckwith Weidman Syndrome (BWS). Differential diagnosis includes partial molar pregnancy, complete mole with co-existing normal fetus, hemangioma, subchorionic hematoma, confined placental mosaicism and hydropic complications. Histologic features, ancillary studies including immunohistochemistry and genetic testing are helpful in differentiating PMD. PMD is an underdiagnosed entity with increased risk of premature delivery and intrauterine fetal death. It is pertinent for the clinicians to be aware of this entity for optimal patient management.